US Foreign Policy towards India in Post 9/11 Era: Implications for South Asian Security - Usman Shaukat; Mussarat Jabeen (Journal of Political Studies, 2019)
The strategic balance of the South Asia is maintained through two basic factors; first, Nuclear Deterrence which includes nuclear doctrines, missile development and nuclear weapons. Second important feature is “role of major powers”. It is obvious fact that strategic stability of South Asia is maintained through the US involvement especially after nuclearization hence, balance of power. Even if we discuss the case of Pakistan it is obvious that most of the Pakistan‟s defense related equipment are either produced by the US or obtained through its financial and political assistance. In this discussion if we ignore the role of China then it will be negligence at our part but facts are never denied and we must know that America has major contributions in strengthening the Pakistan defense mechanism. In this scenario US tilt towards India will put sever impacts on Pakistan militarily and ultimately will lead the whole South Asian region towards the imbalance of power. Because convergence of US interests with India will ultimately lead US to prefer India on political, defense and economic fronts vis-a-vis other states of the region and its side effects will have far reaching implications for regional security.